Do climate and soil influence phenotypic variability in leaf litter, microbial decomposition and shredder consumption? - Graça, M. A. S. (2014)
We tested the hypothesis that water stress and soil nutrient availability drive leaf-litter quality for decomposers and detritivores by relating chemical and physical leaf-litter properties and decomposability of Alnus glutinosa and Quercus robur, sampled together with edaphic parameters, across wide European climatic gradients. By regressing principal components analysis of leaf traits [N, P, condensed tannins, lignin, specific leaf area (SLA)] against environmental and soil parameters, we found that: (1) In Q. robur the condensed tannin and lignin contents increased and SLA decreased with precipitation, annual range of temperature, and soil N content, whereas leaf P increased with soil P and temperature; (2) In A. glutinosa leaves N, P, and SLA decreased and condensed tannins increased with temperature, annual range of temperature, and decreasing soil P. On the other hand, leaf P and condensed tannins increased and SLA decreased with minimum annual precipitation and towards sites with low temperature. We selected contrasting leaves in terms of quality to test decomposition and invertebrate consumption. There were intraspecific differences in microbial decomposition rates (field, Q. robur) and consumption by shredders (laboratory, A. glutinosa). We conclude that decomposition rates across ecosystems could be partially governed by climate and soil properties, affecting litter quality and therefore decomposers and detritivores. Under scenarios of global warming and increased nutrients, these results suggest we can expect species-specific changes in leaf-litter properties most likely resulting in slow decomposition with increased variance in temperatures and accelerated decomposition with P increase.